Pengembangan Lembar Kerja Peserta Didik Berbasis Project Based Learning Di Kelas Tiga - Na'imah, Lailatun; Fauziyah, Nur; Khikmiyah, Fatimatul (Postulat : Jurnal Inovasi Pendidikan Matematika, 2024)
The aim of this research is to use LKPD-based learning media with the PjBL learning model with valid, effective and practical fraction material. The research method used by researchers in this study uses the ADDIE paradigm, which is an abbreviation for "Analysis, Design, Development, Implementation and Evaluation," in the context of research and development (R&D). Student response surveys, learning outcomes assessments, and media expert surveys and all that play a role in validating research procedures. The research results show that the LKPD learning media based on Project Based Learning (PjBL) is an instrument that can be used for valid, effective and practical learning.